Influence of temperature and blanching duration on quality of minimally-processed carrot (Daucus carota, l.) during freeze storage - Santosa (2018)
The objective of this study is to identify the quality of minimally-processed carrot during freezing storage toward temperature and blanching time. The result of research shows that minimmally-processed carrot at freezing storage could maintain its good quality till 14 days. Damaging of tissue and the loss of turgor pressure in carrot slice occur after 14 days. Meanwhile, in the prevailing condition, the blanched carrot could maintain till 2 days only. It is indicated by the soft-slice, rotten smell, and decay of slice. The best hardness obtained on sample for 14-day stored at 70°C, in 2 minutes and 4 minutes viz. 130.234 kPa. The best condition for maintaining amount of vitamin C content of carrot was found at 70°C as long as 4 minutes viz. 0.022%. The treatment of temperature and blanching time during the freezing storage gave the effect toward weight loss, diameter-shrink but not giving the effect on the water level, hardness, and vitamin C.